Duration of fever in pediatric patients hospitalized with Community Acquired Pneumonia in a reference center for infectious diseases - Fernando Galeano; Lourdes Estigarribia; Gabriela Sanabria; Antonio Arbo (Open Journal of Tropical Medicine - Peertechz Publications, 2020)
Introduction: Community acquired pneumonia (CAP) is an important cause of global morbidity and mortality, especially in developing countries, more frequently affecting children under 5 years of age. Few studies in the region have analyzed the total duration of fever days in relation to the presence of complications of the disease. Objective: To determine the total fever days in patients admitted to the Institute of Tropical Medicine with a diagnosis of CAP, in relation to the presence of complications such as pleural effusion. Material and methods: Retrospective, descriptive, cross-sectional study, including clinical records of pediatric patients under 16 years of age, admitted to the Institute of Tropical Medicine from January 2015 to December 2017. Epidemiological, clinical, and laboratory data were included and evolutionary. Results: 433 patients with a diagnosis of CAP were included. The mean age was 32.6 ± 38.3 months. The age distribution was presented as follows: from 0 to 23 months, 252 (58.2%) patients, from 24 to 59 months, 97 (22.4%) and ≥ 60 months, 84 (19.4%) patients. Two hundred thirteen patients (49.2%) were female and 220 (50.8%) were male (1:1 ratio). The presence of pleural effusion was verified in 17.3% of patients (75/433). The average white blood cell count was 16102 ± 11549 cel/mm3; the hemoglobin and hematocrit averages were 10.5 ± 2.1 g / dL and 32 ± 5.8%, respectively. Platelets presented a mean of 397911 ± 186023 / mm3 with C-reactive protein positive in 318 patients (73.4%). The presence of bacteremia was verified in 28 (6.5%) patients. Severe hemodynamic compromise, verified by the presence of shock on admission, was found in 69 (15.9%) of the patients, requiring hospitalization in the Pediatric Intensive Care Unit (PICU) 149 patients (34.4%). The requirement of mechanical respiratory assistance occurred in 21.9% (95/433) of the cases, the average stay in assisted ventilation being 3.2 ± 5.3 days. The presence of comorbidities was 13.4% (58/433). The mortality found was 6.5% (28/433). Some microorganism was isolated in 12.7% of cases (55/433). Pneumococcus was found in 12/55 (21.8%), Staphylococcus aureus in 27/51 (49.1%) patients. The presence of bacteremia was verified in 28 (6.5%) patients. In pleural fluid, the germ was identified in 32.7% of cases (18/55) patients. In relation to fever, 79% (342/433) of the patients presented it, the total duration of the fever being 4.5 ± 4.6 (Range: 1 - 32), yielding the same value in cases with effusion pleural (4.6 ± 4.6 days Range: 0-27) and in cases of bacteremic pneumonia (4.6 ± 4.6 days Range: 1-27) (p> 0.05). Conclusion: Community-acquired pneumonia represents high morbidity and mortality, with greater involvement in children younger than 5 years, with a significant requirement for intensive care. Fever is very frequent, not observing a difference in its duration in relation to the presence of pleural effusion or bacteremia.